Outcomes of total hip arthroplasty in patients with primary immune thrombocytopenia. Issue 1 (December 2015) - Lim, Seung-Jae; Yeo, Ingwon; Park, Chan-Woo; Moon, Young-Wan; Park, Youn-Soo
Abstract Background Immune thrombocytopenia (ITP) is an immune-mediated acquired disease that is characterized by a decrease in the platelet count and an increased risk of bleeding. There is little information in the literature about the results of major joint replacement surgery in patients with ITP. The aim of this study was to report on the results of total hip arthroplasty (THA) in patients with primary ITP. Methods We retrospectively identified 15 THAs performed in 11 patients with primary ITP. The study group was matched (1:2) to a non-ITP control group of 30 THAs in 22 patients. According to the perioperative hematologic evaluation, blood management interventions were performed. All procedures were performed by a single surgeon and all patients received cementless components with ceramic-on-ceramic bearing. Mean duration of follow-up was 7.1 years (range, 2–13). Results No significant differences were found between the two groups with regard to mean operative time, intraoperative blood loss, amount of closed suction drainage, length of hospital stay, and readmission rate. However, the proportion of patients requiring transfusion of packed red blood cells and/or platelet concentrate was higher in the ITP group when compared to the non-ITP group. Mean Harris hip score improved from 49.5 points preoperatively to 93.4 points at the final follow-up and no hips were revised for loosening or osteolysis in the ITP group. No significant differences were found between the two groups with respect to mean postoperative Harris hip scores and complication rates. Conclusions Our study showed encouraging clinical and radiographic results of THA in patients with ITP without increased risk of adverse events compared to those in patients without ITP. On the basis of these findings, we suggest that modern cementless THA might be a viable treatment for achieving functional improvement in patients with ITP and end-stage hip disease.